Association between parity and risk of suicide among parous women - Yang, Chun-Yuh (Canadian Medical Association, 2010)
BACKGROUND: There are limited empirical data to support the theory of a protective effect of parenthood against suicide, as proposed by Durkheim in 1897. I conducted this study to examine whether there is an association between parity and risk of death from suicide among women. METHODS: The study cohort consisted of 1 292 462 women in Taiwan who had a first live birth between Jan. 1, 1978, and Dec. 31, 1987. The women were followed up from the date of their first birth to Dec. 31, 2007. Their vital status was ascertained by means of linking records with data from a computerized mortality database. Cox proportional hazard regression models were used to estimate hazard ratios of death from suicide associated with parity. RESULTS: There were 2252 deaths from suicide during 32 464 187 person-years of follow-up. Suicide-related mortality was 6.94 per 100 000 person-years. After adjustment for age at first birth, marital status, years of schooling and place of delivery, the adjusted hazard ratio was 0.61 (95% confidence interval [CI] 0.54–0.68) among women with two live births and 0.40 (95% CI 0.35–0.45) among those with three or more live births, compared with women who had one live birth. I observed a significantly decreasing trend in adjusted hazard ratios of suicide with increasing parity. INTERPRETATION: This study provides evidence to support Durkheim’s hypothesis that parenthood confers a protective effect against suicide.